PERLINDUNGAN KEKAYAAN INTELEKTUAL KOMUNAL PASCA TERBITNYA PERATURAN PEMERINTAH NOMOR 56 TAHUN 2022 TENTANG KEKAYAAN INTELEKTUAL KOMUNAL - Dian Nurfitri (Jurnal De Lege Ferenda Trisakti, 2023)
The protection of communal intellectual property currently has specific regulation through Government Regulation Number 56 Year 2022 on Communal Intellectual Property. Prior to this regulation, protection of communal intellectual property was only regulated through regulation of other intellectual property. In this regulation there are new concept of communal intellectual property protection such as the concept of inclusive moral right which and integration of communal intellectual property which is to protect communal intellectual property with defensif model. The concept of communal intellectual property protection are developing invarious countries, especially countries in Latin America and Africa